Peran Manajerial Dalam Meningkatkan Kualitas Kerja Karyawan Pada Kantor Bulog Cabang Langsa - Prabowo, Aji; Astuti, Yulina; Tarlis, Andi (EKOBIMA, 2024)
In managing an organization or company, good governance or managerial is needed. Basic knowledge of management needs to be understood and applied well by managers so that it will be very helpful in carrying out their duties in an effort to achieve organizational goals. The study entitled The Role of Managers in Improving the Quality of Employee Work at the Bulog Langsa Branch Office. The objectives of the study are a) to find out how the role of managers is in improving the quality of work of employees of the Bulog Public Company, Langsa Branch Office. b) to find out what efforts are made by managers to improve the quality of work of employees of the Bulog Public Company, Langsa Branch Office. The research methodology is qualitative where the role of the researcher is as a key instrument in collecting data and interpreting data. The results of the study are the implementation of performance management at the Bulog Public Company, Langsa Branch Office, basically using public service performance management that has been implemented by the Bulog Public Company, Jakarta Head Office. However, to carry out the performance of employees of the Bulog Public Company, Langsa Branch Office, it is necessary to implement work planning, division of work into sub-sections, and strategies used by the Bulog Public Company, Langsa Branch Office in an effort to achieve employee performance.